Using Social Media in Schools - Hensley, Matt; Waters, Stewart (Research in Social Sciences and Technology, 2023)
Social media is becoming more eminently woven into the sociocultural fabric of global societies in the 21st century. From emerging platforms and ever-evolving multimodal features, to algorithmic changes and privacy concerns, social media is indubitably shaping the frontier of how people communicate, interact, and perceive the world around them. Using social media in schools is, of course, not a new phenomenon. However, given unabating advances in digital technology coupled with shifting user demands, social media is constantly in flux. Thus, staying abreast of social media trends and uses in the field of education is a critical endeavor and merits on-going conversations.